The Transformation of Software Product Management and The Role of Product Manager in the Age of Generative AI - Goel, Abhinav (Digital Repository of Theses, 2026)
In the era of rapid technological advancement, generative artificial intelligence (GenAI) is reshaping the landscape of software product management (SPM). This dissertation explores the multifaceted impact of GenAI on the role of product managers, team dynamics, ethical considerations, and the software development lifecycle. Through a mixed-methods approach involving quantitative surveys and qualitative interviews with over 100 professionals across diverse industries, the study investigates how GenAI adoption influences collaboration, decision-making, and strategic planning. The findings reveal that GenAI significantly enhances team efficiency, creativity, and stakeholder satisfaction by automating routine tasks, accelerating prototyping, and enabling data-driven insights. Product managers are transitioning into AI-augmented strategists, requiring new competencies in prompt engineering, ethical oversight, and cross-functional collaboration. The study also highlights the ethical challenges posed by GenAI, including data privacy, algorithmic bias, and regulatory compliance, emphasizing the need for robust governance frameworks. By integrating theoretical models such as the Technology Acceptance Model (TAM), Innovation Diffusion Theory, and Socio-Technical Systems Theory, the research provides a comprehensive framework for understanding and guiding the responsible integration of GenAI in product management. The dissertation concludes with actionable recommendations for organizations to upskill teams, redefine workflows, and foster ethical AI adoption. Keywords: Generative AI, Software Product Management, Product Manager, Agile Product Development, Prompt Engineering, AI Adoption